Turmeric- from spice rack to medicine cabinet? - Stoyanovich, Carlee; Mercier, Michelle (Université d'Ottawa | University of Ottawa, 2015)
Background: Alzheimer’s disease (“AD”) is a terminal, neurodegenerative disorder that affects the elderly. Numerous research studies show the existence of a number of markers of inflammation in the AD brain, suggesting that AD is an inflammatory response and that it significantly contributes to it’s own pathogenesis [1]. Anti-inflammatory pharmaceuticals have been shown to limit inflammation but not without side effects. A natural source of an anti-inflammatory exists in the Indian herb turmeric. The lowest rates of validated AD are found in rural India, a population known for its turmeric consumption [2]. Objective: This review intends to synthesize the best available evidence associating the therapeutic potential of turmeric with the successful treatment of AD in the elder (>60) population. Methods: A literature review was conducted and relevant peer-reviewed journal articles from CINAHL, PubMed and ScienceDirect were collected and prioritized based on inclusion criteria. Two independent researchers assessed the articles for relevancy and the inter-rater reliability was 100%. Results: A total of 12 studies were included for review and results were relatively consistent among them. The literature shows a clear association between turmeric and a significant reduction in the psychological and behavioral symptoms of this form of dementia. In experimental studies turmeric has been shown to successfully reduce the beta-amyloid plaque burden as well as other AD proteins. Conclusion: Since the turmeric plant itself cannot be patented, it’s benefits are difficult to put into practice and thus epidemiological research is limited. Available research synthesized in this review has generated results indicating that naturally occurring turmeric has beneficial potential for the treatment of Alzheimer’s patients. Further human studies is needed to positively ascertain these results, with consideration of bioavailability, safety and tolerability in the target populations.